The key to surgery of rare maxillofacial fracture: A case report - Dania, Mutia Rizka; Susilo, Dwi Hari (Edelweiss Applied Science and Technology, 2025)
The naso-orbital-ethmoid complex (NOE) fracture is a rare maxillofacial fracture, with an incidence of about 5% among all maxillofacial fractures. NOE complex damage may result in severe facial dysfunction and malformation. We report the case of an 18-year-old Indonesian woman presenting with pain on the right side of her face after falling from a motorcycle in a traffic accident 3 days prior to her admission to the hospital. There was no history of unconsciousness. Physical examination revealed periorbital hematoma, periorbital bleeding, crepitation in the superior and inferior orbits, and a positive bowstring test. A head CT 3D reconstruction was evaluated and showed a right type III NOE fracture. An elective open reduction and internal fixation were performed. The management of NOE complex fractures is challenging and requires comprehensive clinical examination and radiographic analysis to assess the type and severity of the fracture. Immediate and proper reconstruction can yield better results.